Modern Teaching Methods in Teaching English - Kenjabaev J. A. (Scientific Trends, 2024)
This article discusses the requirements for using digital technologies and Internet resources in the process of teaching foreign languages. In particular, it is highlighted the importance of systematic selection of training manuals to achieve specific goals set by the professor. Over the years different science, theories, and learning styles were developed in terms of teaching foreign languages. You won’t find the best, the one and only method of teaching English to kids or adults. Choosing the proper teaching style depends on students’ skills and abilities. So in this article, we listed some fresh ideas on how to learn a new language and how to choose the right method of teaching English. Always remember to tailor the teaching method to your students’ interests and needs. Also, with the right motivation to learn English, the students are more likely to succeed. So in order to choose the right method of teaching English to adults or children, start with understanding why a person needs or wants to learn the language and then focus on the best technique to achieve their goal.
Keywords: Modern education, computerization, digital technologies, selection of teaching aids.